COVID-19, UPAH, DAN PENGANGGURAN: STUDI EMPIRIS DI INDONESIA - Lestari Agusalim; Agnia Zakia Putri (Bina Ekonomi, 2023)
Unemployment is one of the problems faced by every country, and Indonesia is no exception. The opened unemployment rate during the Covid-19 pandemic increased dramatically compared to the previous year. Many factors affect the increase in the unemployment rate, one of which is wage policy. This study aims to analyze labor conditions in Indonesia before and during Covid-19 and analyze the effect of wages on unemployment before and during the pandemic in Indonesia. The analytical method used, namely the fixed effect model, with panel data for 12 years (2010-2021) in 33 provinces in Indonesia. The results obtained in general are that an increase in wages reduces unemployment, but if wages are increased during the Covid-19 pandemic, it will increase unemployment in Indonesia.